Factors associated with the successful establishment of breastmilk feeding among very low birth weight infants - Zainudin, Zurina; Azlisham, Nadiah; Nunis, Melissa Anne; Syed Abdullah, Farah Inaz; Abang Abdullah, Aisha Fadhillah (Universiti Putra Malaysia Press, 2024)
Introduction: Despite the widely recognised benefits of breastfeeding, preterm newborns globally exhibit lower breastfeeding rates compared to term infants. This study aims to ascertain the prevalence of breast milk feeding among VLBW infants and to evaluate the factors associated with successful breast milk feeding in this specific population. Materials and methods: A cross-sectional study was conducted involving 111 mothers who gave birth to premature infants with birth weights less than 1500 g between March and December 2020. This investigation took place in two tertiary Neonatal Intensive Care Units. Data encompassing maternal, perinatal, and neonatal characteristics were extracted from medical records and subjected to analysis using SPSS version 25. Results: Among the 111 participating mothers, only 44 (39.6%) successfully provided expressed breast milk (EBM) for their infants’ initial feeds, and a mere 31 (28.0%) sustained adequate EBM provision until their infants attained full enteral feeding. The achievement of a successful breast milk feeding establishment demonstrated substantial correlations with higher maternal income (p = 0.023) and the timing of initiating enteral feeds (p = 0.037). Conclusion: The prevalence of breast milk feeding initiation and establishment among VLBW infants was found to be remarkably low. The potential influence of the demanding Covid-19 pandemic context during the study period cannot be ignored. It is imperative to intensify efforts to investigate the underlying causes to facilitate the swift and effective implementation of quality improvement interventions. Future research initiatives are essential to uncovering additional confounding factors that might influence the successful rate of breast milk feeding among VLBW infants.